Pelvic organ prolapse. Issue 12 (December 2016) - Gray, Thomas G; McVey, Sarah; Green, Jill; Saxena, Anupama; Patel, Daksha
Pelvic organ prolapse is the descent of one or more of the pelvic organs, (including the bladder, uterus and rectum) from their normal anatomical position into the vaginal canal in women. This is a result of failure of the fascial, muscular and ligamentous supports of the pelvic organs and is a common problem encountered in primary care. Pelvic organ prolapse can have a profound and significant impact on quality of life, and it is important for GPs to understand how to diagnose and manage women with this condition. The majority of women presenting with pelvic organ prolapse are suitable for initial management in a primary care setting.